IMPACT OF REALIZED INVESTMENTS IN NEW FIXED ASSETS ON GROSS DOMESTIC PRODUCT IN SERBIA - Grujić Vučkovski, Biljana; Paraušić, Vesna; Kljajić, Nataša (Economics of Agriculture, 2023)
The research subject is the analysis of the impact of the value of realized investments in new fixed assets on the gross domestic product (GDP) of Serbia in the period from 2012 to 2021. The research was conducted with the aim of determining which economic activity, according to the value of realized investments, contributes the most to the creation of the value of Serbia’s GDP. The defined goal was realized by applying the multiple regression method, and the starting model contained the value of realized investments in four activities, which are: manufacturing; electricity, gas, steam and air conditioning supply; transportation and storage; agriculture, forestry and fishing. The occurrence of multicollinearity between independent variables was checked by the tolerance coefficient, VIF coefficients and Eigen values, and their values indicate the presence of weak multicollinearity, which is a consequence of the impact of realized investments in agriculture, forestry and fishing. The result of the set regression model shows that the greatest contribution to the creation of Serbia’s GDP is made by the realized investment value in the electricity, gas, steam and air conditioning supply (Standardized Beta Coefficients 0.687, Sig. = 0.012).